2017
DOI: 10.1002/mbo3.515
|View full text |Cite
|
Sign up to set email alerts
|

Genomic insights of Pannonibacter phragmitetus strain 31801 isolated from a patient with a liver abscess

Abstract: Pannonibacter phragmitetus is a bioremediation reagent for the detoxification of heavy metals and polycyclic aromatic compounds (PAHs) while it rarely infects healthy populations. However, infection by the opportunistic pathogen P. phragmitetus complicates diagnosis and treatments, and poses a serious threat to immunocompromised patients owing to its multidrug resistance. Unfortunately, genome features, antimicrobial resistance, and virulence potentials in P. phragmitetus have not been reported before. A predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…A few similar strains of Pannonibacter phragmitetus were isolated and most of the related studies were conducted regarding their ability to reduce Cr(VI) in soil with high Cr(VI) concentrations, to detoxify polycyclic aromatic hydrocarbons under extreme conditions and their drug resistance to elucidate antibiotic resistance and infectivity mechanisms etc. (Zhou et al 2017; Chai et al 2019). To the best of our knowledge, only one study was conducted to evaluate the denitrification capacity of similar strains of Pannonibacter phragmitetus .…”
Section: Discussionmentioning
confidence: 99%
“…A few similar strains of Pannonibacter phragmitetus were isolated and most of the related studies were conducted regarding their ability to reduce Cr(VI) in soil with high Cr(VI) concentrations, to detoxify polycyclic aromatic hydrocarbons under extreme conditions and their drug resistance to elucidate antibiotic resistance and infectivity mechanisms etc. (Zhou et al 2017; Chai et al 2019). To the best of our knowledge, only one study was conducted to evaluate the denitrification capacity of similar strains of Pannonibacter phragmitetus .…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella pneumoniae and P. phragmitetus isolated from petroleum-contaminated waste mud pit were known to be effective in the bioremediation process. Previous studies indicated that K. pneumoniae plays an active role in the biodegradation of petroleum [24] and P. phragmitetus is effective in the detoxification of heavy metals and PAHs [30].…”
Section: Identification Of Bacteriamentioning
confidence: 99%
“…However, You et al [28] clearly showed that K. pneumoniae only biodegraded hydrocarbons in the range of C 10 -C 14 in diesel. Zhou et al [30] reported that Pannonibacter phragmitetus was resistant to extreme environmental conditions such as hot springs, high alkaline conditions and high salt concentration and plays a role in the detoxification of PAHs and heavy metal chrome reduction in these environmental conditions. Acinetobacter sp.…”
Section: Biodegradation Of N-alkane Fractions In Petroleummentioning
confidence: 99%
“…For instance, Pannonibacter was one of the most abundant animal putative pathogens among the grasslands, shrublands, and woodlands (Figure 5a), which could be used as a bioremediation agent for the detoxification of heavy metals and polycyclic aromatic compounds (PAHs), while rarely infect healthy populations. However, the infection caused by the opportunistic pathogen Pannonibacter can complicate diagnosis and treatment and pose a serious threat to immunocompromised patients due to its multidrug resistance [64]. In addition to animal pathogens, there were a variety of plant pathogens in the urban green spaces (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%